قياس مدى امتثال السلطات المالية الليبية بمتطلبات القيد الزمني للميزانية العامة دراسة تحليلية للاستدامة المالية باستخدام نموذج (BOHN) - دلعاب أبوبكر خليفة; بو الساكت سليمان شعيب (Scientific Journal of University of Benghazi, 2022)
This study aims to measure the extent to which the financial authorities in Libya maintain to the requirements of the time-restriction of the public budget during the time period (1980-2020). In purpose to achieve the objective of the study, the Distributed Autoregressive Linear (ARDL) technique is applied on the annual data of the Libyan economy. Results obtained revealed an existence of an inverse relationship between the public budget surplus and public debt, as well as, an existence of the same relationship between temporary government expenditure and the business cycle indicator and between the public budget surplus, which contradicts an assumption of the (BOHN) model on fiscal sustainability. Therefore, this results confirm an unsustainability of fiscal policy of the Libyan economy during the study period, in other words, the failure of the financial authorities in Libya to comply with the requirements of the time-restriction of the public budget, which indicates the growing levels of public debt in a way that could threaten the solvency of the state in meeting its financial obligations. In the future.